Aerobic oxidative dehydrogenation of N-heterocycles catalyzed by cobalt porphyrin. Issue 10 (7th March 2018) - Zhou, Weiyou; Chen, Dongwei; Sun, Fu'an; Qian, Junfeng; He, Mingyang; Chen, Qun
Graphical abstract: Highlights: An efficient catalytic procedure was found for the oxidative dehydrogenation of N -heterocycles. Cobalt porphyrin can catalyze the aerobic dehydrogenation without any additives. The catalytic system can tolerate various substrates. Abstract: An efficient catalytic procedure has been developed for the aerobic oxidative dehydrogenation of N -heterocycles by cobalt porphyrin in the absence of any additives. The catalytic system could tolerate various 1, 2, 3, 4-tetrahydroquinoline derivatives and some other N -heterocycles. The corresponding N -heteroaromatics could be obtained in 59–86% yields. The mechanism investigation suggested that the aerobic oxidative dehydrogenation might proceed with imine intermediate through radical paths.